Dynamic capabilities and their relations with elements of digital transformation in Portugal - Mendonça, Cláudio Márcio Campos de (2018)
The objective of the article was to identify as relations between IoT, Big Data and Artificial Intelligence with the microfoundations of the dynamic capabilities. It was characterized as an exploratory, descriptive and inferential research, with a quantitative approach. In non-parametric tests (Chi-square / Spearman correlation), in Portuguese companies, totaling 137 respondents with valid questionnaires (only business and IT managers) were applied. It has been shown that as 3 technologies, IoT, Big Data and IA, in different proportions of performance, are large in the 3 microfoundations of our dynamic capabilities. The highlight was for the performance presented by Big Data in the Seising microfoundation. The highest correlations were observed for the Seising microfoundation, with emphasis on the strong correlation between IoT and Big Data and moderate correlations between Big Data and AI.